Крестный отец: роман : перевод с английского / А. Пьюзо - Пьюзо Марио (Полипринт, 1993)
Экземпляры: аб. ЦБ (20191202) / Инвентарный номер: 8198 / Цена: / Сис.шифр: 84(4/8) / Авт.знак: П 96 / ББК: 84(7Сое)